How successful is the College of Technological Studies, Kuwait, in reducing dependence on expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
No one can deny the role of technical and vocational education in the world of work. Technical and vocational education would improve productivity, increase in wages, promote self-employment, and provide an opportunity for practicing talent and creativity in work place. It is an ultimate venue for youth to gain the necessary knowledge, skills and attitudes that are mostly needed by industries and business. Indeed, it is different from a formal education where students spend a certain time in real work environment to interact with machines and tools. Technical and vocational education would allow students to work in workshops and laboratories and provide them with the ability to transfer with they learn in classrooms, workshops, and laboratories into real work place. Developing countries (e.g., Kuwait, United Arab Emirates, Qatar), has thoroughly realized and appreciate the role of technical and vocational education in reducing the dependence on expatriates, particularly in essential sectors of the economy (e.g., oil, electricity and water, constructions). Kuwait, as a developing country has recognized and appreciate the need to reduce dependence on expatriates by forging the College of Technological Studies, CTS. The main objective of the College of Technological Studies, Kuwait, is preparing students for the world of work by enhancing the level of student’s knowledge, skills and attitudes that are mostly needed by local industries and business. The research paper focuses on identifying and examining the CTS student’s perception towards the quality of teaching and learning. In addition to, examining industrial perception towards the standard of the CTS graduates. The oil sector and the Ministry of Electricity and Water will be selected to represent the recipients of CTS graduates. The research is based on extensive field work that encompasses a review of the related literature, questionnaires, and an interview with a sample of heads of departments at the CTS. Interviews will be also conducted with the CTS graduates’ supervisor in selected industries. Finally, the research will argue that unless the CTS recognize and appreciate the value of building a strong linkage with industry, its contribution in tackling the shortage of skilled and semi-skilled indigenous manpower will be below the government expectations, thus continuing relaying on expatriates for years ahead.